Patterns of young hockey players’ mastering of skills to perform special complex coordination exercises - Pavlov, A.S.; Bizyaev, V.V.; Frolova, N.N.; Pozdeeva, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the pattern of young hockey players’ mastering of skills in performing special complex coordination motor acts – using the example of mastering the exercise ‘Slalom with a puck.’ Methods and structure of the study. The research was conducted with the participation of hockey players from a sports school of different age groups. At the end of the preparatory and competitive periods, testing was carried out using the exercises ‘Slalom without a puck’ and ‘Slalom with a puck.’ For each individual age group of hockey players, the group-average indicators of the difference in results of the players’ performance of the specified exercises were calculated, characterising the degrees of mastery of the complex coordination exercise ‘Slalom with a puck.’ A comparison of these indicators was carried out, correlated with data on the number of training sessions of hockey teams in which the exercise ‘Slalom with a puck’ was used. Results and conclusions. A pattern was identified in young hockey players’ mastering of skills in performing special complex coordination motor acts, according to which the degree of mastery of these motor acts by hockey players depends on the number of training sessions in which they are performed by the players.